2017
DOI: 10.1148/radiol.2016160626
|View full text |Cite
|
Sign up to set email alerts
|

CT Measures of Bone Mineral Density and Muscle Mass Can Be Used to Predict Noncancer Death in Men with Prostate Cancer

Abstract: Purpose To determine if computed tomographic (CT) metrics of bone mineral density and muscle mass can improve the prediction of noncancer death in men with localized prostate cancer. Materials and Methods Institutional review board approval was obtained, with waiver of informed consent. All patients who underwent radiation therapy for localized prostate cancer between 2001 and 2012 with height, weight, and past medical history documented and who underwent CT that included the L4-5 vertebral interspace were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 37 publications
0
47
1
Order By: Relevance
“…Therefore, no additional radiation exposure was incurred in our evaluation of sarcopenia. The measurements were simple to perform using commercially available software, which did not add additional cost (33). In addition, previous studies (36,37) have revealed that underweight patients with LACC (BMI < 18.5 kg/ m 2 ) have a lower OS than normal weight or obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no additional radiation exposure was incurred in our evaluation of sarcopenia. The measurements were simple to perform using commercially available software, which did not add additional cost (33). In addition, previous studies (36,37) have revealed that underweight patients with LACC (BMI < 18.5 kg/ m 2 ) have a lower OS than normal weight or obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Two consecutive transverse CT images extending from L3 to the iliac crest were analyzed using Varian Eclipse software (Varian Medical Systems Inc.; ref. 33), which contains a number of tools that are useful for delineating and analyzing specific regions of interest. The skeletal muscle area includes the psoas, paraspinal, transversus abdominis, rectus abdominis, and internal and external oblique muscles.…”
Section: Ct-based Body Composition Analysismentioning
confidence: 99%
“…CT image parameters included the following information: contrast‐enhanced, 5 mm slice thickness, 120 kVp, and approximately 290 mA. Two consecutive axial CT images extending from the third lumbar to the iliac crest were analysed using the Varian Eclipse software (Varian Medical Systems Inc., Palo Alto, CA, USA) . The skeletal muscle area (including psoas, paraspinal, transversus abdominis, rectus abdominis, and internal and external oblique muscles) was calculated by using Hounsfield unit (HU) thresholds of −29 and +150 .…”
Section: Methodsmentioning
confidence: 99%
“…Two consecutive axial CT images extending from the third lumbar to the iliac crest were analysed using the Varian Eclipse software (Varian Medical Systems Inc., Palo Alto, CA, USA). 55 The skeletal muscle area (including psoas, paraspinal, transversus abdominis, rectus abdominis, and internal and external oblique muscles) was calculated by using Hounsfield unit (HU) thresholds of À29 and +150. 27,28,56 The mean skeletal muscle radiation attenuation of the entire cross-sectional muscle area was reported as SMD.…”
Section: Computed Tomography-based Body Composition Analysismentioning
confidence: 99%
“…Two consecutive transverse CT images extending from L3 to the iliac crest were analysed using the Varian Eclipse software (Varian Medical Systems Inc., Palo Alto, CA, USA) [24]. Predetermined Hounsfield unit (HU) thresholds were −29 to +150 HU for skeletal muscle, −50 to −150 HU for visceral adipose tissue, and −30 to −190 HU for subcutaneous and intermuscular adipose tissue [14,15,20].…”
Section: Computed Tomography-based Body Composition Analysismentioning
confidence: 99%